Evaluating the Effectiveness of the SQ3R Learning Model on Students’ Islamic Religious Education Outcomes - Aprilian, Lucky Yoga; Baharudin, Baharudin; Azizah, Nurul; Zulaikhah, Siti; Yusnita, Erni (Papanda Publisher, 2025)
This study aimed to examine the effectiveness of the SQ3R learning model on students’ cognitive learning outcomes in Islamic Religious Education (IRE) for seventh-grade students at SMP Negeri 1 Bandar Lampung. A quasi-experimental method with a posttest-only control group design was employed. The sample comprised two randomly selected classes: an experimental group (N = 32) taught using the SQ3R model and a control group (N = 32) taught using conventional methods. Data were collected through a validated and reliable multiple-choice posttest assessing cognitive domains of understanding (C2), analyzing (C4), and evaluating (C6). Data analysis included normality testing (Kolmogorov-Smirnov), homogeneity of variance (Levene’s test), independent samples t-test, and effect size calculation (Cohen’s d). Results revealed a statistically significant difference between groups (t(62) = 2.71, p = 0.009), with the experimental group achieving a higher mean score (M = 79.15, SD = 6.10) compared to the control group (M = 73.20, SD = 7.30). The effect size (Cohen’s d = 0.88) indicated a large effect. These findings confirm that the SQ3R model significantly enhances students’ cognitive learning outcomes, particularly in higher-order thinking skills. The study supports implementing the SQ3R learning strategy as a practical approach to improve academic performance in Islamic Religious Education.